Clinical utility of dopamine transporter single photon emission CT (DaT-SPECT) with (123I) ioflupane in diagnosis of parkinsonian syndromes. Issue 11 (13th March 2013) - Bajaj, Nin; Hauser, Robert A; Grachev, Igor D
Abstract : The diagnosis of movement disorders including Parkinson's disease (PD) and essential tremor is determined through clinical assessment. The difficulty with diagnosis of early PD has been highlighted in several recent clinical trials. Studies have suggested relatively high clinical diagnostic error rates for PD and essential tremor. This review was undertaken to clarify the utility of DaT-SPECT imaging with ( 123 I)ioflupane (DaTSCAN or DaTscan or ( 123 I)FP-CIT) in assisting practitioners in their clinical decision making by visualising the dopamine transporter in parkinsonian cases. In some patients with suspected parkinsonian syndromes, SPECT imaging with ( 123 I)ioflupane is useful to assist in the diagnosis and to help guide prognosis and treatment decisions, including avoiding medications that are unlikely to provide benefit. Clinicians ordering ( 123 I)ioflupane SPECT should be aware of its limitations and pitfalls and should order scans when there is diagnostic uncertainty or when the scan will be helpful in clinical decision making.